Effect of pomegranate (Punica granatum L.) peels to seeds ratios and supercritical carbon dioxide extraction conditions on extraction yield and antioxidant activity - Tan, Wei Kiat (2018)
Processing of pomegranates produces large amount of by-products and creates some waste-disposal problem. The non-edible parts of a pomegranate (Punica granatum L.), including peels and seeds, are the by-product of pomegranate processing industry and considered as waste. It has been reported that the peels and seeds contain a wide range of nutritional value and bioactive compounds. Extraction is one way to recover the valuable compounds from the waste product. Supercritical carbon dioxide (SC-CO₂) extraction, which can perform extraction at low temperature and absence of harmful chemicals, is proposed as the green technology method to perform extraction on both pomegranate peels and seeds together. The main objective of the work is to study effect of different ratios of pomegranate peels and seeds, and different extraction condition on the yield and antioxidant activity by using SC-CO₂. Extraction from five different peels to seeds ratios (A-0:100, B-25:75, C-50:50, D-75:25, and E-100:0) and full factorial design with four different pressures (10, 20, 30 and 40 MPa) and temperatures (30, 40, 50 and 60 °C) were carried out. With the presence of peels in the extraction, synergic effect on the global yield was observed when comparing to expected global yield, which was up to 37.6% increment. The most suitable ratio for extraction was Ratio C, which was 50% of peels to 50% of seeds, had significantly higher global yield (11.7%) and higher yield increment percentage (32.6%) compared to other ratios. Ratio C was also found to have the significantly highest TPC (0.60 ± 0.04 mg GAE/g extract) among the three mixture extracts. As for the full factorial design approach, 40 MPa and 40 °C with the highest global yield (11.5%) was chosen as the most suitable extraction condition as it also produced significantly higher TPC and DPPH values, which the values were comparable to the second highest value with no significant differences. 54 tentative compounds were being detected from extract of highest yield condition based on database from KNApSAcK, a comprehensive species-metabolite relationship database developed by Nara Institute of Science and Technology. The first order model was found to be the best fitting model for experimental yield data at 40 MPa, with R² range of 0.9935-0.9984. The activation energy, EA of the extraction was found to be 11.8996 kJ/mol. The empirical extraction model for 40 MPa supercritical carbon dioxide extractions on 50:50 pomegranate peels and seeds was developed.